Dampak Prosedur dan Reviu Inspektorat Terhadap Peningkatan Akuntabilitas LKPD Provinsi Banten - Jessi Chintiaranita Listira; Septian Bayu Kristanto (InFestasi, 2018)
This research wants to analyze the effect of procedure and review inspectorate towards accountability of Local Government Financial Statement (LGFS) Banten Province. Researchers interested in extreme changes of audit opinion on LGFS Banten in period 2013 to 2016. The change from disclaimer opinion to qualified opinion, and then unqualified opinions in short period are crucial. The analyze result of LGFS in 2016 shows that the review procedures from The Audit Board of Republic Indonesia (BPK RI) are reasonably assured. Those reviews are effecting the increasing of accountability of LGFS in period 2015 and 2016. This result means Banten Province has been covered their LGFS quality. The suggestion in this research is to optimize the role of Government Internal Supervisory Apparatus (APIP) to maintain the quality and accountability of LGFS in the future.